Supportive Expressive Therapy for Generalized Anxiety Disorder in Client with Burst Fractures Frankle - C (Sains Humanika, 2021)
This article presents a case study of a client with burst fracture frankle-C. This client also has generalized anxiety disorder. Supportive expressive therapy was used as therapeutic intervention. A burst fracture is a type of traumatic spinal injury in which a vertebra breaks from a high-energy axial load. The psychological problems often experienced by persons with body disabilities, such as burst fracture francle-C. This is a quantitative research with a single client. While collecting the data, used interview methods (autoanamnesa and alloanamnesa), observation, and psychological tests (DAP, BAUM, BAI, and Sack’s Sentence Completion Test). The result before the practitioner gives the Beck Anxiety Inventory, the client’s anxiety is 20 (moderate anxiety), after intervention 15 (mild anxiety), and follow up 11 (mild anxiety). In addition, the client is also better able to understand his condition and the problems being faced. The catharsis process that has happened so far makes the client able to express what he feels and thinks so as to make the client feel the perceived burden is reduced. Clients can begin to open up to family members at home and conduct simple chats when parents are at home to reduce the habit of repression that was previously done. The technique and also the process of the therapeutic process along the therapy session will be discussed in detail.
Keywords: Supportive Expressive Therapy, Client, Burst Fracture Frankle-C, Generalized Anxiety Disorder, Traumatic Spinal Injury